A globally ubiquitous symbiont can drive experimental host evolution. Issue 15 (14th June 2021) - Bates, Kieran. A.; Bolton, Jai S.; King, Kayla C.
Abstract: Organisms harbour myriad microbes which can be parasitic or protective against harm. The costs and benefits resulting from these symbiotic relationships can be context‐dependent, but the evolutionary consequences to hosts of these transitions remain unclear. Here, we mapped the Leucobacter genus across 13, 715 microbiome samples (163 studies) to reveal a global distribution as a free‐living microbe or a symbiont of animals and plants. We showed that across geographically distant locations (South Africa, France, Cape Verde), Leucobacter isolates vary substantially in their virulence to an associated animal host, Caenorhabditis nematodes. We further found that multiple Leucobacter sequence variants co‐occur in wild Caenorhabditis spp. which combined with natural variation in virulence provides real‐world potential for Leucobacter community composition to influence host fitness. We examined this by competing C. elegans genotypes that differed in susceptibility to different Leucobacter species in an evolution experiment. One Leucobacter species was found to be host‐protective against another, virulent parasitic species. We tested the impact of host genetic background and Leucobacter community composition on patterns of host‐based defence evolution. We found host genotypes conferring defence against the parasitic species were maintained during infection. However, when hosts were protected during coinfection, host‐based defences were nearly lost from the population. Overall, our results provide insight into the role of community context in shaping host evolution during symbioses.